Modelación del THD en los sistemas de alimentación residencial - Lincango Sigcha, Edgar Guillermo (2015)
Faced with the growing interest in the care of the quality of energy in the residential electrical service and its scope in the concept of distribution, the purpose of this paper is obtain a mathematical modeling which will serve to obtain the characteristic equation that comes out of a common residence and comes to the distribution network, this residence will have several electronic equipment which have non-linear loads that are used daily. Calculate the rate of total harmonic distortion is also another parameter that we can find with this modeling quickly and easily, For this calculation of the THD we'll use mathematical tools such as the Fourier series and the Monte Carlo simulation for the latter which will enable us to conduct a convergence between the signals of different types of loads are connected in parallel are admitted to the network in a different time of use, and then comparing these results between homes of three types as you can be a common residence, a residence of senior resources and a residence of low resource. We will have the help of the Fluke power analyzer 43 B single phase with which we are going to find the most characteristic harmonics present when using the VCR, tv, microwave oven, the computer with your monitor, and the fluorescent lamp. This undertaken for a interface is used to step the historic generated in the analyzer to carry to an Excel file, to then enter these data as a file to MATLAB and generate the different types of waves of current and voltage with which we will achieve the desired model.